Laura Ingalls Wilder and Rose Wilder Lane : authorship, place, time, and culture - Miller, John E., 1945-2020 (University of Missouri Press, 2008)
"One of America's leading authorities on Laura Ingalls Wilder and Rose Wilder Lane combine analyses of both women to explore their collaborative process and how their books reflect the authors' view of place, time, and culture, expanding the critical discussion of Wilder and Lane beyond the Little house"--Provided by publisher.